Pengembangan Multimedia Interaktif Berbasis Aplikasi Canva dan Wordwall Pada Materi Keliling dan Luas Bangun Datar di Kelas V Sekolah Dasar : Penelitian dan Pengembangan (R&D) - Arina Aprilia Fidel; Yetti Ariani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the less than optimal implementation of technology-based interactive multimedia. Teachers primarily use textbooks, concrete media, PowerPoint presentations, and simple instructional videos, leading to less engaging and monotonous learning experiences. This is due to limitations in knowledge, skills, and time for creating instructional media. This research aims to develop valid, practical, and effective interactive multimedia based on Canva and Wordwall applications. The type of research used in this study is Research and Development (R&D). The model employed is the ADDIE model, which consists of five phases: Analysis, Design, Development, Implementation, and Evaluation. Data analysis techniques include preliminary study analysis (interviews, observations, student needs analysis), validity, practicality, and effectiveness. The validity test yielded very valid results, with media validation at 100% (Very Valid), material validation at 100% (Very Valid), and language validation at 100% (Very Valid). The practicality test at the SD Negeri 05 Padang Pasir trial school, based on teacher response questionnaires, showed 100% (Very Practical), and student responses indicated 98.8% (Very Practical). The effectiveness test at the SD Negeri 15 Anduring and SD Negeri 25 Lubuk Lintah research schools, based on pre-test and post-test scores, showed an increase in learning outcomes. Thus, it can be concluded that the